Sex differences in fatigability of dynamic contractions - Hunter, S. K. (Experimental Physiology, 2015)
Women are usually less fatigable than men during single limb isometric contractions primarily due to sex-related differences in contractile mechanisms. It is less clear whether these sex differences in muscle fatigue occur for dynamic fatiguing tasks. This review highlights new findings that the sex difference in fatigability dynamic shortening contractions with a single limb is dependent on the contraction velocity and the muscle group involved. Recent studies demonstrate that women are less fatigable than men for a dynamic task for (1) the elbow flexor muscles at slow but not high velocity contractions, and (2) the knee extensor muscles when muscle fatigue was quantified as a reduction in the maximal voluntary isometric contraction (MVIC) force after the dynamic fatiguing task. Contractile mechanisms are responsible for the sex difference in muscle fatigue of the dynamic contractions with no evidence for a sex difference in the reduction in voluntary activation (i.e. central fatigue). Thus, these findings indicate that the sex difference in muscle fatigue of dynamic contractions is task specific. These data also challenge the assumption that men and women respond similarly to training and rehabilitation that involve fatiguing contractions to overload the neuromuscular system. There is, however, a tremendous opportunity for conducting high impact studies to gain insight into those factors that define the sex-based differences in muscle fatigue during dynamic tasks. Such studies can inform of the boundaries to human performance in both men and women during athletic endeavours, ergonomic tasks, and in rehabilitation.